Cloning, expression of Vibrio alginolyticus outer membrane protein‐OmpU gene and its potential application as vaccine in crimson snapper, Lutjanus erythropterus Bloch. Issue 8 (6th February 2013) - Cai, S H; Lu, Y S; Wu, Z H; Jian, J C
Abstract The outer membrane proteins of the marine aquatic animal pathogen, Vibrio alginolyticus, play an important role in the virulence of the bacterium and are potential candidates for vaccine development. In this study, the gene encoding an outer membrane protein‐OmpU was cloned and expressed in Escherichia coli. Polyclonal antibodies were raised in rabbits against the purified recombinant OmpU, and the reaction of the antibody was confirmed by Western blotting using the isolated OmpU and the recombinant OmpU of V. alginolyticus. To analyze the immunogenicity of the recombinant OmpU, crimson snapper, Lutjanus erythropterus Bloch, were immunized by intraperitoneal injection, and antibody response was assessed by the enzyme‐linked immunosorbent assay (ELISA). The results demonstrated that the recombinant OmpU produced an observable antibody response in all sera of the vaccinated fish. The vaccinated fish were challenged by virulent V. alginolyticus and observed to have high resistance to infection. These results indicate that the recombinant OmpU is an effective vaccine candidate against V. alginolyticus in L. erythropterus.